Changes in the structure of a savanna forest over a six-year period in the Amazon-Cerrado transition, Mato Grosso state, Brazil - Daniel David Franczak; Beatriz Schwantes Marimon; Ben Hur Marimon-Junior; Henrique Augusto Mews; Leandro Maracahipes; Edmar Almeida de Oliveira (Rodriguésia)
Abstract Vegetation changes in transition zones are still poorly studied. Changes in the vegetation structure of a savanna forest (cerradão) were assessed in the Amazon-Cerrado transition (14º42'2.3"S; 52º21'2.6"W), eastern Mato Grosso, within a period of six years (2002, 2005 and 2008). In 2002, fifty plots of 10 × 10 m were set up, where all trees with DSH30 ≥ 5 cm were measured; in 2005 and 2008 the plots were re-inventoried. In 2008, 84 species from 70 genera and 37 families were sampled; absolute density was 1,998 individuals/ha and basal area was 25.95 m2.ha-1. On the one hand, the absolute density of live individuals decreased from 2005 to 2008 (2,066 individuals/ha); on the other hand, the basal area increased in 2008 compared to 2005 (23.56 m2.ha-1) and 2002 (1,884 individuals/ha and 21.38 m2.ha-1). The species with the highest importance value in the period were Hirtella glandulosa, Tachigali vulgaris and Xylopia aromatica. Except for these three species, all other species underwent hierarchic changes in the importance value, indicating that most species frequently alternate. Community structure exhibited changes throughout the period; hence, we suggest investigations on the role of T. vulgaris in these changes, since environmental conditions caused by gap opening from the fall of senile individuals of this pioneer species with a short life cycle may contribute to community dynamics.